#207 Formulation and characterization of fast dissolving oral films delivering model antihyperglycemic drug - Bhattacharya, Muniraj; De, Pintu Kumar (Journal of Pharmaceutical Chemistry, 2022)
Fast dissolving oral films are drug delivery systems of the new day having one of the highest patient compliance, safety & are economical than most other dosage forms. Hydrophilic polymers, when in contact with water, get hydrated and thus show drug release if used as a vehicle. Hydrophilic polymers also show an adherence property post hydration. Thus the hydrating and adhering properties of hydrophilic polymers make it most suitable for producing fast dissolving oral film. Fast dissolving oral films are made to be administered into the buccal cavity of humans as the buccal cavity if having saliva and saliva helps to hydrate the films leading to drug release. The buccal cavity in humans has a very high amount of blood supply system, thus aiding in faster drug entrance into the blood circulation. The fast dissolving oral films are capable of initiating drug release within seconds, without chewing and drinking. The instant bioavailability achieved bypassing the fast pass metabolism also adds as a salient feature. Various compositions of different polymers lead to differences in the drug release rate of the films. Polymers such as hydroxypropyl methylcellulose (HPMC); polyvinyl alcohol (PVA); ethyl cellulose; sodium carboxymethyl cellulose are some common hydrophilic polymers that are used to produce fast dissolving oral films. Drugs with a shorter half-life and having the small intestine as their main site of absorption and maintenance of adequate plasma levels of the drug can be achieved by systemic drug delivery, for active pharmaceutical ingredients having high solubility and low permeability resulting to produce low bioavailability. Solvent casting, semi-solid casting; hot-melt extrusion; solid dispersion extrusion are some common methods of production of fast dissolving oral films. Immediate onset of action in a shorter period with improved bioavailability marked fast dissolving oral film, a dosage form of choice. Though the films are not a good choice for water-insoluble drugs. Five different formulations with HPMC and PVA as polymers in different raions are prepared using the solvent casting method. Propylene glycol is used as the plasticizer. Films are cast in molds, dried, and kept in moisture-free storage away from sunlight at room temperature. After producing the fast dissolving oral films, they are passed through a series of evaluations such as weight (ranging between 0.216-0.152 gm), thickness (ranging between 0.11-0.074 mm), folding endurance (ranging between broken at 185.5 to 250 not broken), swelling% (ranging between 651.61 to 1020%), drug content (ranging between 98 to 99%), disintegration time (ranging between 15 sec to 50 sec) and in-vitro drug release (ranging between 59 to 83% drug release at 15 min). All data were recorded in triplicates and found that all films passed the required evaluations. It was found that the amount of increase in hydroxypropyl methylcellulose gives faster drug release compared to polyvinyl alcohol.